A metabolic associated fatty liver disease risk variant in MBOAT7 regulates toll like receptor induced outcomes - Jawaher Alharthi; Ali Bayoumi; Khaled Thabet; Ziyan Pan; Brian S. Gloss; Olivier Latchoumanin; Mischa Lundberg; Natalie A. Twine; Duncan McLeod; Shafi Alenizi; Leon A. Adams; Martin Weltman; et al. (Nature Communications, 2022)
Hyperactivation of the toll-like receptors (TLRs) have been implicated as risk factors for more severe forms of disease in COVID-19 and metabolic (dysfunction) associated fatty liver disease (MAFLD). Here the authors report that MBOAT7 is reduced in macrophages of patients with MAFLD and COVID-19, and acts as a negative regulator of TLR signalling.